Author Correction: Temporal dynamics in viral shedding and transmissibility of COVID-19 - He, Xi; Lau, Eric H. Y.; Wu, Peng; Deng, Xilong; Wang, Jian; Hao, Xinxin; Lau, Yiu Chung; Wong, Jessica Y.; Guan, Yujuan; Tan, Xinghua; Mo, Xiaoneng; Chen, Yanqing; et al. (Nature medicine, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.An amendment to this paper has been published and can be accessed via a link at the top of the paper.